Behavior management of uncooperative children with attention deficit hyperactivity disorder symptoms: Penatalaksanaan perilaku anak tidak kooperatif dengan gejala attention deficit hyperactivity disorder - Silvana, Intan Renita; Jeffrey (Makassar Dental Journal PDGI Makassar, 2024)
A common psychiatric problem called attention deficit hyperactivity disorder (ADHD) is characterised by impulsivity resulting in behavioural problems and a very short attention span and is associated with childhood. This study evaluates the management of behaviour in the management of uncooperative children with ADHD symptoms using various behaviour modification techniques. A PubMed and Google Scholar publication search was conducted and 5 articles published 2014-2024 were reviewed. It was found that combined therapy, behavioural therapy and pharmacotherapy, can help dental management in children with ADHD symp-ptoms. It was concluded that dentists should be knowledgeable about behaviour management, including tell-show-do, distrac-tion, modelling, brain function training, and medications prescribed for children, as well as side effects and possible drug inter-actions with sedatives included in the dental treatment protocol.